Athenaea velutina: isolamento e caracterização de lactonas esteroidais polioxigenadas (vitanolídeos) - Mendonça, Lavosyer da Silva (2024)
Withanolides are a class of secondary metabolites particularly found in plants from the Solanaceae family, restricted to the Solanoideae subfamily. This compound's class has a structure derived from the ergostane framework which can provide steroidal δ- or γ-lactones. Withanolides have shown a high pharmacological interest and are considered promising molecules as drug candidates as the withaferin A. Therefore, this work aims to continue the study of extracts from the leaves of Athenaea velutina (Solanaceae) focusing on the chemical investigation of the ethanol extract (AVFE). chromatographic fractionation of AVFE resulted in the isolation of six compounds. An analysis of 1H and 13C NMR (1D and 2D) spectra allowed the structure elucidation of the new withanolides: 3-O-[α-L-rhamnopyranosyl-(1→4)-β-D-glucopyranosyl]-tuboanoside A (AV20), 3-O-[α-L-rhamnopyranosyl-(1→4)-β-D-glucopyranosyl]-1-acetyl-5,24-dienolide (AV21) and 16-hydroxypubesenolide (AV24) as well as the known withanolides pubesenolide (AV22), (20S,22R)-3α,6α-epoxy-4β,5β,27-trihydroxy-1-oxyvita-24-enolide (AV23) and 6α-chloro-4β,5β,27α-trihydroxy -1-oxo-22R-vita-2,24-dienolide (AV19). An anti-inflammatory screening was conducted using the two major withanolides, analyzing their effects on the viability of RAW 264.7 cells and their ability to inhibit cellular nitric oxide (NO) production. While withanolide AV20 exhibited pro-inflammatory activity by increasing nitrite production in LPS-stimulated macrophages, AV21 showed anti-inflammatory action by reducing these levels.